Effects of heat treatment on fish oil extraction process using a single screw expeller - Bako, Tanko; Umogbai, Victor Imolemhe; Awulu , John Okanagba (Journal of Postharvest Technology, 2024)
Effects of heating temperature and duration on yield and quality (free fatty acids value, saponification value, para-anisidine value and  peroxide value) of oil extracted from fish using a single screw expeller was studied. Heating temperature and duration were 60, 70, 80  and 90 °C and 5, 10, 15 and 20 minutes respectively. All data collected were subjected to analysis of variance (ANOVA) to test for  significant effects at 95 % confidence limit. When significant difference was observed, treatment means were separated using the F LSD. The oil yield ranged between 17.2 % and 21.6 %, free fatty acid values (2.2–4.5 %), saponification values (134-189 mgKOH/g),  para-anisidine values (7.3-12.2 mEq/kg) and peroxide values (8.1–11.7 mEqO2/kg). The treatments have significant effects on oil yield,  free fatty acid value, saponification value, para-anisidine value and peroxide value or at p
Keywords: Oil extraction; fish oil; screw expeller; process parameters